Pollen analysis of honeys from the northwest of Argentina: Province of Jujuy - Sánchez, Ana Carina (2017)
The palynological characterization of 157 honey samples from three northwesternregions of Argentina (Prepuna, Yungas and Chaco) are presented todetermine their botanical origin and species associations to be able to definetheir geographic origin. Samples were harvested during 2003-2011 andprocessed by means of melissopalynological conventional techniques. Onehundred and nine pollen types were identified. Representative pollen types witha frequency of occurrence greater than 50% in descending order of importanceare: Salix humboldtiana, Allophylus edulis, Baccharis sp., Solanaceae,Eucalyptus sp., Schinus sp., Brassicaceae, Papilionoideae, Celtis sp.,Scutia/Condalia type y Parapiptadenia excelsa. The most important monofloralhoneys are from the following: Salix humboldtiana, Scutia/Condalia type,Allophylus edulis, Baccharis sp., Blepharocalyx salicifolius, Gleditsiaamorphoides, Myrtaceae, Sicyos sp., Ziziphus mistol, Schinopsis type,Agonandra excelsa, Anadenathera colubrina var cebil, Mimosa debilis all ofthem native species and among introduced species: Eucalyptus sp., Citrus sp.and Tithonia sp. Three apicultural zones and their corresponding association ofspecies indicators were determined: Zone I: Prepuna: Caesalpinia trichocarpa,Prosopis ferox, Schinus areira, Baccharis sp., Buddleja sp. and Mutisieae. ZoneII: Yungas: Myrtaceae, Parapiptadenia excelsa, Baccharis sp., Salixhumboldtiana, Allophylus edulis, Scutia/Condalia type y Zanthoxylum coco.Zone III: Transitional area Yungas-Chaco: Prosopis sp. Salix humboldtiana,Schinus sp., Anadenanthera colubrina var cebil y Allophylus edulis.